Workshop pembuatan perangkat pengajaran Kurikulum 2013 dan penguatan konsep dasar Matematika pada Kelompok Kerja Guru SD - zaid zainal; Hasnah Hasnah; Fajar Fajar (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Curriculum of 2013 (K-13) requires the teaching for every subject at an integrated level, known as thematic teaching, which means that on one theme may link several subjects to that particular subject. After evaluating the implementation of K-13, the revised edition provides exceptions for teaching mathematics. The main problem faced by Math teachers is their understanding of basic concepts in mathematics still low, there are still various materials that they do not know and they often difficult to solve particular math problems. This program aims to help upper class teachers in the 7th cluster of Ujung district in Pare-Pare in understanding the basic concepts of Mathematics, helping to solve problems that are considered difficult and Math modules that are difficult to teach. This program is an intensive workshop for teaching Math. The method used in this workshop is interactive coaching. The trainer and the participants are working together to solve Math problems and the participants also equipped with independent tasks which indicate their progress in knowledge and understanding of basic concept of Mathematics.